Lost in Transmission? : The Effectiveness of Monetary Policy Transmission Channels in the GCC Countries - Cevik, Serhan (IMF Working Papers; Working Paper ;, 2012)
This paper empirically investigates the effectiveness of monetary policy transmission in the Gulf Cooperation Council (GCC) countries using a structural vector autoregressive model. The results indicate that the interest rate and bank lending channels are relatively effective in influencing non-hydrocarbon output and consumer prices, while the exchange rate channel does not appear to play an important role as a monetary transmission mechanism because of the pegged exchange rate regimes. The empirical analysis suggests that policy measures and structural reforms - strengthening financial intermediation and facilitating the development of liquid domestic capital markets - would advance the effectiveness of monetary transmission mechanisms in the GCC countries.